Investigating the Effect of Time of Collection on the Antioxidant Values of Mistletoes (Viscum album) Grown on Orange Tree - Akinlami O. Omokehinde; Hammed O. Oloyede (Pharmaceutical Research - Recent Advances and Trends Vol. 4, 2024)
Background and Aim: Viscum album (mistletoe) is a hemi-parasitic shrub, frequently globular in shape. Viscum album is well recognized as a medicinal plant due to its beneficial effects, including anti-tumor activity, antioxidant, anti-inflammatory, anti-hepatotoxic, hypoglycemic, and antimicrobial properties as well as for lowering blood pressure. This study aims to investigate the effect of time of collection on the antioxidant values of mistletoes (Viscum album) grown on orange trees. Methods: Aqueous leaf extracts of different times of harvest of Viscum album were prepared and standard methods were used to determine quantitatively the antioxidants values in the plant extracts. The fresh leaves of the mistletoe plant (Viscum album) from the host plant Orange tree were obtained from a research farm of Adeyemi College of Education, Ondo, Ondo State, Nigeria. The total phenolic content was determined using the Folin-Ciocalteau reagent. The free radical scavenging activities of aqueous extract were measured with stable 1, 1-diphenyl- 2-picryl hydrazyl radical (DPPH) spectrophotometrically. Results: In the experiments, the total phenol content in aqueous leaves extracts of Viscum album was 19.5840 mg/g, at 6: 00 am, 55.4061 mg/g at 1:00 pm and the value 86.3682 mg/g recorded at 7:00 pm. The value of 0.344 mg/g was recorded for flavonoids at 6:00 am while the value of 0.676 mg/g was observed at 1:00 pm and at 7:00 pm it was 1.458 mg/g. The % of inhibition of DPPH content in aqueous leaves extracts of Viscum album was 36.819 mg/g, at 6: 00 am, 49.213 mg/g at 1:00 pm and the value of 61.203 mg/g was recorded at 7:00 pm. The antioxidants values were significant (P =0.05) when compared time of plant collection. Conclusion: The results showed that the antioxidant values depend on the time of collection which was maximum when the leaves were obtained at dawn. It is therefore advisable that the use of this extract in herbal medicine should be encouraged and the plant should be plucked at dawn to maximise the antioxidant potential of the mistletoes.